Chemical predictive modeling of ethyl-p-methoxycinnamate and synthesis of natural lotion from kencur (Kaempferia galanga L.) as sunscreen agents - Salmahaminati; Noor Fitri; Yuvia Rafi Kusuma (Universitas Lancang Kuning, 2023)
Solar radiation is essential for the evolution of life on earth. Solar radiation, including ultraviolet radiation (UV), reaches the earth's surface. The sun emits three types of UV radiation: UVA, UVB, and UVC, which have beneficial and harmful effects on the human body. The most important benefit is the synthesis of vitamin D in the skin. However, UVB radiation also causes direct photochemical damage to DNA. This study aimed to investigate the ability of the compound ethyl-p-methoxycinnamate (EPMS) that is available in kencur as a sunscreen agent through computational chemistry studies using the Hartree-Fock (HF) method and time-dependent density functional theory (TD-DFT) and perform synthesis of lotion from kencur extract. The investigation began with creating a molecular model of a sunscreen agent optimized for geometry using the HF method and continued with spectrum analysis using TD-DFT. The study's results showed that the analysis of the EPMS spectrum could be used as a natural UVB shield. In addition, the synthesis of lotion from kencur rhizome made using oil and water phases showed organoleptic, pH, homogeneity, and spreadability test results fitted according to the Indonesian National Standard (SNI) 16-4399-1996. It indicated that kencur lotion could potentially be used as a sunscreen agent.